The Social Hipervulnerability of the Subject of Law From Carrilho Community case Study, of Itabaiana Municipality/ SE - Carvalho, José Lucas Santos (2016)
The objective is to discuss the vulnerability of the subject of law by different dimensions, emphasizing possibilities in which multitude of risks turns into hipervulnerability. In Brazil, consumer rights doctrine and jurisprudence consolidated the protection of the hyposufficient, extended to other sectors. But there are situations with overlapping vulnerabilities, especially in the social dimension, like the cashew processors in Carrilho/SE. The article uses theoretical and legal research method - legal and methodological exploratory-type, of doctrine and academic texts content analysis, and research results carried out with the community, to be developed the concept and applicability of social hipervulnerability.